Allergen Avoidance in Allergic Asthma - Cipriani, Francesca; Calamelli, Elisabetta; Ricci, Giampaolo (Frontiers in Pediatrics, 2017)
Allergic asthma is the most frequent disease among the chronic respiratory disorders in paediatric age with an important social impact. In the last years, many effort have been made to identify preventive effective approaches to get a better control of symptoms and to obtain the best future outcomes for the patients. In patients with allergic asthma triggered by the exposure to indoor allergens, the avoidance is the first intervention to prevent the appearance or the worsening of bronchial symptoms. This review article summarized the most recent evidence from literature about the efficacy of specific control interventions for the most important allergens. Even if a wide spectrum of interventions has been suggested and may help to reduce exposure to trigger allergy for sensitized patients suffering from respiratory allergy, evidence supporting the efficacy of these approaches is still weak and subject of controversy. However, the exposure control to specific airborne allergens is still widely recommended and may be effective as part of a holistic approach to reduce the severity of allergic respiratory symptoms in sensitized individuals.